Teaching Out Loud: Critical Literacy, Intergenerational Professional Development, and Educational Transformation in a Teacher Inquiry Community. Issue 4 (1st October 2020) - Crawford-Garrett, Katherine; Carbajal, Damon R.; Short, Amanda; Simpson, Kahlil; Meyer, Emilia; Deck-Stevens, Eleanor
ABSTRACT: This paper draws on practitioner inquiry and participatory action research methodologies to recount how five K-12 educators, who inhabit a range of positionalities and levels of teaching experience, engage in a collaborative professional development program, called Teaching Out Loud as they draw upon critical literacy theory and practice to reimagine educational spaces in ways that make schooling more just, humanizing and student-centered. Specifically, we document how these educators name oppressive circumstances, deconstruct power relations, and reconfigure their practice through innovative, critical curricular projects, arguing that alternative conceptions of professional development that center criticality, intergenerationality, and participatory forms of knowledge construction have the potential to transform teacher learning in neoliberal times.